Corporate intelligence as a competitive fighting tool - M. M. Begichev; S. A. Potapov; A. V. Vlasov (Путеводитель предпринимателя)
All existing companies today want not only to remain in the service market, but also to gain a foothold in it, and methodically develop from year to year. And in the modern world, this is simply impossible to imagine without corporate intelligence. Those firms that did not realize this in time simply went bankrupt or their business does not develop, and economic indicators remain in one place from year to year. Today, there is a wide variety of ways of business intelligence in the world. All types of competitive intelligence can be divided into two large groups: direct and indirect business intelligence. Let’s look at each of them in more detail. A separate subspecies is business intelligence, which can relate to both indirect and direct intelligence, depending on the surrounding circumstances.